¿Out of sight, out of mind¿: Modern economics, social interactions, and Smith¿s sympathy (2012)
After having reviewed some of the recent advances in Economics trying to incorporate new elements in our understanding of human interactions, we aim at contributing to this line of research using Adam Smith¿s system of sympathy. The features Smith attributes to the intersubjective identification mechanism of sympathy lead not only to conceive the construction of a community but also the possibility of exclusion of some of its members. The asymmetry of sympathy allows explaining emulation of those seen as more fortunate as well as the exclusion of those perceived as miserable. Through a formal representation we try to illustrate the phenomena of inclusion and exclusion present in intersubjetive relations and the construction of communities.